(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Photoelectric devices, such as solar panels, play a pivotal role in the generation of sustainable energy. However, their efficiency is significantly influenced by various climatic conditions. This article explores and evaluates algorithms designed for calculating the power output of photoelectric devices under different environmental circumstances. The goal is to enhance the understanding of how these algorithms can be leveraged to optimize energy harvesting across diverse climates.